Neural evidence for enhanced attention to mistakes among school-aged children with a growth mindset. (April 2017) - Schroder, Hans S.; Fisher, Megan E.; Lin, Yanli; Lo, Sharon L.; Danovitch, Judith H.; Moser, Jason S.
Abstract: Individuals who believe intelligence is malleable (a growth mindset) are better able to bounce back from failures than those who believe intelligence is immutable. Event-related potential (ERP) studies among adults suggest this resilience is related to increased attention allocation to errors. Whether this mechanism is present among young children remains unknown, however. We therefore evaluated error-monitoring ERPs among 123 school-aged children while they completed a child-friendly go/no-go task. As expected, higher attention allocation to errors (indexed by larger error positivity, Pe) predicted higher post-error accuracy. Moreover, replicating adult work, growth mindset was related to greater attention to mistakes (larger Pe) and higher post-error accuracy. Exploratory moderation analyses revealed that growth mindset increased post-error accuracy for children who did not attend to their errors. Together, these results demonstrate the combined role of growth mindset and neural mechanisms of attention allocation in bouncing back after failure among young children.